[tex]d)\\\\\begin{cases}x-y-6=0\\y=-x^2 \end{cases}\\\\\begin{cases}x- (-x^2)-6=0\\y=-x^2 \end{cases}\\\\\begin{cases}x- (-x^2)-6=0\\y=-x^2 \end{cases}\\\\x^2+x-6=0\\\\\Delta =b^2-4ac=1^2-4*1*(-6)= 1+24=25\\\\\sqrt{\Delta }=\sqrt{25}=5[/tex]
[tex]x_{1}=\frac{-b-\sqrt{\Delta }}{2a}=\frac{-1-5}{2*1}=\frac{-6}{2}=-3 \\\\x_{2}=\frac{-b+\sqrt{\Delta }}{2a}=\frac{-1+5}{2*1}=\frac{4}{2}=2\\\\\begin{cases} x=-3\\y=-x^2\end{cases}\ \ \ lub\ \ \ \ \begin{cases} x=2\\y=-x^2\end{cases}\\\\\begin{cases} x=-3\\y=- (-3)^2\end{cases}\ \ \ lub\ \ \ \ \begin{cases} x=2\\y=-2^2\end{cases}\\\\\begin{cases} x=-3\\y=-9\end{cases}\ \ \ lub\ \ \ \ \begin{cases} x=2\\y=-4\end{cases}[/tex]
[tex]interpretacja\ geometryczna:\\\\\begin{cases}x-y-6=0\\y=-x^2 \end{cases}\\\\\begin{cases}y=x -6 \\y=-x^2 \end{cases}[/tex]